Among-family variations of solid wood properties in 4-year-old Eucalyptus camaldulensis trees selected for pulpwood production in Thailand. (2nd January 2017) - Ishiguri, F.; Diloksumpun, S.; Tanabe, J.; Ohshima, J.; Iizuka, K.; Yokota, S.
Abstract : Solid wood properties were examined in eight half-sib families of 4-year-old Eucalyptus camaldulensis trees selected for pulpwood production in Thailand. The effects of radial growth rate on solid wood properties were also discussed. The mean values of green moisture content (MC) and basic density (BD) at 1.2 m heights in each family ranged from 86.3 to 106.6% and from 0.49 to 0.57 g cm −3, respectively. Significant among-family differences were found in MC, BD and maximum height of interlocked grain (IG). However, no significant correlations were found between stem diameter and solid wood properties, with the exception of MC and BD at a 5.2 m height, and IG. Based on the results obtained, it is suggested that superior E. camaldulensis trees, with respect to both growth characteristics and solid wood properties, can be selected for pulpwood production.